DEVELOPING INTERACTIVE E-MODULES FOR LANGUAGE LEARNING IN PRIMARY EDUCATION: AN ADDIE-ORIENTED DESIGN SYNTHESIS - Nurmairina Nurmairina; Dinda Yarshal; Nurul Fatehah Binti Norhazaruddin (Sensei International Journal of Education and Linguistic, 2026)
Nowadays the students in primary school already use handphone and laptop, so the teacher can also make the material in digital form. But many e-modules are only the textbook that is changed into PDF, so the students just read and there is no interaction. This article discusses the development of interactive e-modules for language learning in primary education. The method used is literature review from books and journals about e-module, multimedia, and young learners. The result shows that the e-module must have clear objective, interesting picture and audio, exercise with feedback, and also must be easy to be opened by the students. If the e-module is only interesting but not connected with the language objective, the students will only play and not learn. Therefore the teacher and the developer must design the e-module carefully by using the ADDIE model.